The Open Monographs Project - Watson, D (Bodleian Libraries, University of Oxford, 2023)
Open Access mandates have over recent years become a standard part of the academic workflow - Oxford's Act on Acceptance policy requiring the submission to our open access repository (ORA) of journal articles and conference papers. Books have until now largely escaped these expectations, but that is beginning to change. Starting January 2024, the UKRI will mandate open access for funded longform publications, and we can anticipate in coming years there will be more mandates to come, requiring ever greater open availability of longform work like monographs. This will lead to exciting increases in availability and accessibility of academic work, but may also mean academics face new challenges in funding the publication of open access books, dealing with copyright considerations, and engaging with new publishing models – amongst many others. This poster details some of these challenges and the work of the Open Monographs Project in preparing for the arrival of open books.